Extraction and Characterization of Natural Lignocellulosic Fiber from Borassus flabellifer Leaf Sheath - Selvam Seenidurai, Panneer; Thillai Arasu, Ponnusamy; Murugan, Arumugam (Asian Journal of Chemistry, 2022)
A natural lignocellulosic fiber has been extracted from Borassus flabellifer leaf sheath (BFSE) fibers and they characterized for its chemical composition, morphology, crystallinity, density, single fiber tensile strength and thermal property through standard analytical method using Fourier-transform infrared spectroscopy (FTIR), scanning electron microscope (SEM), X-ray diffraction (XRD), pycnometer, universal testing machine and thermogravimetric analysis (TGA). The chemical compositions of BFSF were found as cellulose, hemicellulose and lignin contents of 48.20 ± 0.95, 25.92 ± 0.83 and 23.83 ± 0.34%, respectively. The SEM micrograph confirmed the presence of textured surface of fiber. TGA indicates that the fibers are thermally stable up to 208 ºC. The crystallinity and single fiber tensile strength were calculated as 33.15% and 170-220 MPa, respectively.